Pacific finance sector brief cook islands. (Metro Manila, Philippines Asian Development Bank, 2019)
The Cook Islands financial system includes four commercial banks, a national superannuation fund, an insurance company, several insurance intermediaries, and money changing and remittance businesses. Although the country finance sector performs relatively well, private sector lending declined during 2013-2015 and has yet to return the level in 2012. Two major hurdles to development are the high number of nonperforming loans and the lack of an efficient payment system. To address these, the Cook Islands Credit Bureau was established in late 2017 and the government is currently looking into the viability of the Bank of Cook Islands joining the New Zealand payments system.
Keywords: Finance; Industrial policy; Electronic books